Laboratory Studies on the Production of Asphalt Mixture Bad 22,4 with Pet (Plastic Bottle Fibers) - Claudiu-Ionel Chicuș; Gheorghe Gugiuman; Gelu-Răzvan Gimiga; Cristian Iriciuc Silviu (Romanian Journal of Transport Infrastructure)
Plastic is a versatile and cheap material, but extremely durable and nearly impossible to decompose in nature. Plastic waste is not only a visual pollution issue but also a global health problem, as microplastics enter the food chain, affecting both marine life and humans. Moreover, the mass production of plastic is closely linked to greenhouse gas emissions and the depletion of natural resources. Pollution caused by PET (polyethylene terephthalate) is one of the most severe forms of environmental pollution due to excessive use and inadequate recycling of these materials. PETs are mainly used in the form of containers (bottles), and because of their durability and slow degradation in nature, these objects become a major source of pollution, affecting both terrestrial and aquatic ecosystems.